An optical fiber strain sensor by using of taper based TCF structure. (December 2019) - Zhang, Chuanbiao; Ning, Tigang; Zheng, Jingjing; Xu, Jian; Gao, Xuekai; Lin, Heng; Li, Jing; Pei, Li
Highlights: A compact in-fiber strain sensor based on twin-core fiber. A new taper pulling technique. The proposed device had a maximum interferometric extinction ratio up to 20 dB. High strain sensitivity about 6.11 pm/με. Low temperature sensitivity about 0.69 pm/°C. Abstract: We propose an optical fiber strain sensor consisting of a spliced twin-core fiber (TCF). The sensor structure has two fiber tapers, which are weak taper and T-shaped taper. The taper waist of T-shaped taper is about half-size of the weak taper, but the length of the T-shaped taper is also about half- length of the weak taper. In the sensing structure, core mode and cladding modes of the TCF are excited simultaneously. Two tapered regions around the splicing interfaces can play the roles of splitting and combining the modes in the fiber. In experiment, the proposed device has good quality interferometric spectra, and the highest extinction ratio of 20 dB is achieved. When the stress increases from 0 με to 841.5 με, different wavelength sensitivities of 3.31 pm/με and 6.11 pm/με are achieved. Different intensity sensitivities of 7.5 × 10 −3 dB/με and 9.9 × 10 −3 dB/με are also achieved, respectively. The sensor has shown good test stability and low temperature sensitivity, which is good for precise strain measurement in practical applications.